(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Social sustainability plays a significant role in the entire sustainable framework. It can be described in a variety of ways, such as: The capacity of a city to continue to serve as a long-term viable environment for social interaction, communication, and cultural development. At the same time, it is an aspect of sustainability that is often overlooked. Where the focus is only on the economic and environmental aspects Materials and Methods: This study deals with social sustainability estimation using remote sensing and surveying techniques. The study focuses on Sheikh Fars area, which is in eastern Missan, because of the economic significant of the area. The research hypothesis assumes that Sheikh Fars city is a good social sustainability according to its significance. Results: The results of the questionnaire survey (direct process) were analyzed used collected data (face to face interview) for residents using Likert scale approach. The results indicated that the study area is classified a poorly social sustainable area. as well as its neighboring areas, as they have the same characteristics as the region. Conclusion: In conclusion, this study weakens the first hypothesis, indicating that the Sheikh Fars area is socially unsustainable regardless of its economic significance. The findings show a significant gap between economic and social performance. This emphasizes the importance of incorporating direct social assessments into sustainable development plans.